2014
DOI: 10.1111/adj.12154
|View full text |Cite
|
Sign up to set email alerts
|

Application of three‐dimensional computed tomography in craniofacial clinical practice and research

Abstract: Following the invention of the first computed tomography (CT) scanner in the early 1970s, many innovations in threedimensional (3D) diagnostic imaging technology have occurred, leading to a wide range of applications in craniofacial clinical practice and research. Three-dimensional image analysis provides superior and more detailed information compared with conventional plain two-dimensional (2D) radiography, with the added benefit of 3D printing for preoperative treatment planning and regenerative therapy. Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 103 publications
(138 reference statements)
1
43
0
3
Order By: Relevance
“…Future studies are needed to complement the data on profilometric changes from early erosion with changes in physical and chemical changes of the tooth structures using established and evolving techniques [51][52][53][54][55][56][57][58] in order to provide an holistic assessment of early erosion process. Such an approach will enable quantitative data to be gathered on enamel softening, together with qualitative observations of increased porosity in partially lost and demineralized hydroxyapatite crystals (as displayed in stages 2, 3 and 4 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies are needed to complement the data on profilometric changes from early erosion with changes in physical and chemical changes of the tooth structures using established and evolving techniques [51][52][53][54][55][56][57][58] in order to provide an holistic assessment of early erosion process. Such an approach will enable quantitative data to be gathered on enamel softening, together with qualitative observations of increased porosity in partially lost and demineralized hydroxyapatite crystals (as displayed in stages 2, 3 and 4 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Geol took advantage of CT geometrical scanning to reconstruct the human digital model, but the meshing accuracy of CT-based digitized human anatomical model was very low, it was difficult to ensure the accuracy of model solution results [26]. With the continuous development of CT and 3D reconstruction, especially the technological innovation of 32-row and over, multi-slice spiral CT and dual-source CT, the CT bone 3D imagingresolution keeps increasing, not only the resolution of field of view (FOV) has been significantly improved, the slice thickness could reach the mm level, providing the possibility towards the digitized reconstruction of CT-based 3D data [27,28]. However, the current CT 3D reconstruction of medical imaging is only the different post-processing methods towards the volume images, such as CT surfaceshading reconstruction (SSD), maximum intensity projection (MIP) and multiplanar reconstruction (MPR), etc.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cell delivery-based bone repairing technology, which is currently available in clinic, is still limited to the repairing of focal lesions [5]. In recent years, the high polymer-inorganic substances has become the hotspot in the bone tissue engineering (BTE) research because of its biodegradability and easy 3D processing [6], Alothman et al [7] found that the composite of high-density polyethylene (HDPE)-hydroxyapatite (HA) exhibited the tensile strength as up to [22][23][24][25][26][27][28] MPa and the changes of HA content might adjust the characteristic of composite; Zein et al [8] found that the compressive strength of poly-e-caprolactone (PCL) could reach 4-77 MPa, and the yield strength cold reach 0.4-3.6 MPa when the pore size was 160-700 mm and the porosity was 48-77 %, which was much more suitable for the requirements of BTE.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in computer imaging have revolutionized medical science [23,25,25,26,27] its use in craniofacial deformities and a more comprehensive diagnosis and treatment plan can thus be obtained by this method, improving the treatment outcome. …”
Section: Discussionmentioning
confidence: 99%